Estudo da viabilidade de microrganismo probiótico bifidobacterium lactis em patê de frango com características simbióticas e sua ação na estabilização da oxidação lipídica - Costa, Renata Brum (2012)
The aim of this study was to investigate the viability of Bifidobacterium lactis microorganism as probiotic when applied to pate chicken storage for period of 42 days. The chicken pate was prepared in the laboratory of meat processing of the UFSM Polytechnic College, according to the formulation provided by local industry. A portion of this mass of pate was enriched with unripe banana flour (Musa spp.) constituting a symbiotic food. The culture used was probiotic strain Bifidobacterium lactis 420 (B420), acquired by Danisco do Brasil Ltda. Two different inoculants were made in order to reach the expected final concentration of Log 106 UFC.g-1 and 108 UFC.g-1. Preliminary tests of microorganism resistence at different temperatures in the chicken pate were performed in order to establish the best temperature for the inoculation. The strain of microorganism was tested against different concentrations of NaCl (1.0%, 1.5% and 2.0%) and NaNO2 (150 ppm, 200 ppm and 250 ppm). It was resistant to all tests, including when combined concentrations of these values, but it showing increased sensitivity with increasing concentration. The product developed was evaluated by physical-chemical properties ( proximate composition and TBARS), microbiologic (coliforms at 45ºC, Clostridium perfringens, Staphylococcus coagulase positive, Salmonella sp.) and sensory (color, aroma, flavor and texture). It was found that the product reached all the requirements established by Brazilian legislation regarding chemical composition and microbiological standards. Taking into account the previsions of Brazilian law that establishes the minimum amount of viable probiotic bacteria, in the product ready for consumption, is between 108 to 109 colony forming units, the Bifidobacterium lactis was considered a good probiotic for chicken pate for a period of 21 days only, period is too short considering the shelf-life of the traditional chicken pate, which can reach up to 90 days of refrigerated storage. The determination of lipid oxidation (TBARS) showed that treatments 2 and 3 with the addition of the probiotic microorganism in a concentration of 108 UFC.g-1 obtained more satisfactory results when compared to the control and treatment of an added 106.UFC.g-1 of the probiotic, suggesting that the probiotic microorganisms in certain concentrations have a positive influence on the oxidation of lipids in the chicken pate, putting a "protective effect". Treatments with Bifidobacterium lactis had a good sensory acceptance in attributes, with the exception of treatment 3, which was added unripe banana flour, which changed the color and texture of the product but also impaired the development of Bifidobacterium lactis . In this study, it was found that treatment with the addition of probiotic micro-organism concentration of 108 UFC.g-1 was the best satisfied the initial goals as far as the viability of the probiotic lipídica oxidation stabilization. Althoug of a shelf-life minor, it can be seen that there is the feasibility of the probiotic Bifidobacterium lactis organism in meat products such as cooked chicken pate, which has the acceptance by consumers and can serve as an alternative development of meat products with functional properties.